Multi-trace elements-enriched functional drink accelerates gastric ulcer repair via the HGF/c-Met/STAT3 pathway - Yongnan Piao; Nuoya Wang; Mingji Jin; Jianyu Piao; Mingfeng Han; Zifei Wang; Chunhua Quan; Jishan Yin; Zhonggao Gao; Wenxiang Cui; Shuangqing Wang; Xiuquan Quan (Journal of Functional Foods)
Heavy alcohol consumption can lead to various gastrointestinal disorders, with gastric ulcers being the most prevalent. In this study, we explored the reparative effects of a functional drink (FD) enriched with trace elements (TEs) on ethanol-induced gastric ulcers in rats and elucidated its underlying mechanism. Rats were administered anhydrous ethanol (5 mL/kg) orally to induce gastric ulcers and were then randomly assigned to a model, an omeprazole (OME, 20 mg/kg), FD with low-dose (FD-L), medium-dose (FD-M), high-dose (FD-H), FD without added TEs (FD without TEs), and an omeprazole+low-dose group (OME + L). FD increased the activities of antioxidant factors (T-SOD, GSH, CAT, and IL-10), and decreased the inflammatory factors levels (TNF-α, IL-6, MDA, COX-2, and iNOS) by promoting the HGF/c-Met/STAT3 pathway. It also effectively regulate the abundance and diversity of intestinal flora. Finally, FD reduced the severity of gastric mucosal injury caused by invasive factors, improved the morphological structure of gastric mucosal cells, enhanced the ability of oxidative stress, and inhibited excessive inflammatory response. In addition, the combination of OME and FD-L did not significantly affect the therapeutic efficacy of OME, but reduced its adverse effects. Ultimately, FD presentation had a pro-healing effect on the ethanol-induced gastric ulcer model. In conclusion, FD has a wide range of developmental prospects and offers an attractive approach and protocol for the treatment of clinical gastric ulcers.